Praktik Penghindaran Pajak: Multinasionalitas, Transfer Pricing, dan Good Corporate Governance - Tirana, Kadek Prilia; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi, 2024)
This study aims to determine the effect of multinationality, transfer pricing, independent board of commissioners, institutional ownership, and audit committee on tax avoidance practices. Data sources are obtained from annual reports and financial reports of mining sector companies listed on the Indonesian Stock Exchange in 2018-2021 using the documentation method. The sample was determined by purposive sampling method which resulted in 114 observed data. The data was analyzed using multiple linear regression. The results showed that institutional ownership has a positive effect, but multinationality, transfer pricing, independent board of commissioners and audit committee have no effect on tax avoidance practices. The results of the study are in line with stakeholder theory which states that the more powerful institutional ownership will be the greater its control over the company.